2022
DOI: 10.21203/rs.3.rs-1963644/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High miR-99b expression is associated with cell proliferation and worse patient outcomes in breast cancer

Abstract: Background: Although miR-99b is a known suppressive microRNA in several cancer types, its role in breast cancer is not elucidated. In this study, we examine the clinical relevance of miR-99b expression in breast cancer. Methods: We analyzed microRNA and messenger RNA expressions and their relationships with clinical parameters for 1,961 breast cancer samples from two independent large cohorts, the Cancer Genome Atlas (TCGA) and the Molecular Taxonomy of Breast Cancer International Consortium (METABRIC). Severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Importantly, E2F is a downstream effector of CDK4 and CDK6 on the cell cycle and its overexpression may hamper the activity of CDK4/6i. Moreover, high miR-99b expression was associated with worse patient survival, particularly in HR+/HER2− tumors [23]. Our results seem to support an oncomiR function for this miRNA in patients treated with ET and CDK4/6i.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Importantly, E2F is a downstream effector of CDK4 and CDK6 on the cell cycle and its overexpression may hamper the activity of CDK4/6i. Moreover, high miR-99b expression was associated with worse patient survival, particularly in HR+/HER2− tumors [23]. Our results seem to support an oncomiR function for this miRNA in patients treated with ET and CDK4/6i.…”
Section: Discussionsupporting
confidence: 64%
“…An inverse relationship between the expression of miR-99b-5p and mTOR has been described either in BCCL and tumor specimens [22]. Oppositely, an analysis of two large datasets of breast cancer patients consisting of 1961 cases downloaded from the METABRIC and TCGA databases showed that high miR-99b expression correlated significantly with enriched mTORC1 gene sets and that the mTOR pathway, but no other signaling pathway, was activated in miR-99b-high-expressing breast cancer specimens [23]. In the same datasets, miR-99b-high breast cancer specimens were significantly enriched in three genes related to cell proliferation: E2F targets, the G2/M checkpoint, and mitotic spindle gene sets.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and mRNA expression breast cancer data were obtained from the Cancer Genome Atlas Program (TCGA) (whole database, n = 1090; estrogen receptor positive and human epidermal growth factor receptor negative tumors (ER+ HER2−), n = 593; human epidermal growth factor receptor positive tumors (HER2+), n = 184; and triple negative breast cancer (TNBC), n = 160), the Molecular Taxonomy of Breast Cancer International Consortium (METABRIC) (whole database, n = 1094; ER+ HER2−, n = 1355; HER2+, n = 236; and TNBC, n = 313), and GSE96058 (whole database, n = 3069; ER+ HER2−, n = 2277; HER2+, n = 392; and TNBC, n = 155). These three databases were obtained via the cBioPortal ( (accessed on 9 October 2022)) and the Gene Expression Omnibus (GEO) repository of the United States National Institutes of Health ( (accessed on 9 October 2022)), as previously described [ 32 , 33 ]. Gene expression data from 114 samples of normal breast tissue were obtained from the Genotype-Tissue Expression (GTex) Portal ( (accessed on 9 October 2022)) [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Functional enrichment analysis of the LPP genes ( PLPP1–3 ) was performed by gene set enrichment analysis (GSEA) [ 33 ] on the Molecular Signatures Database Hallmark collection ( (accessed on 9 October 2022)) [ 37 ]. A false discovery rate (FDR) of <0.25 indicated enriched signaling gene sets [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Clinical outcomes and mRNA expression for breast cancer patients were obtained from three large databases: the Cancer Genome Atlas Program (TCGA) (whole database n = 1090; estrogen-receptor-positive and human-epidermal-growth-factor-receptor-negative (ER+ HER2-) n = 593; HER2+ n = 184; triple-negative breast cancer (TNBC) n = 160), the Molecular Taxonomy of Breast Cancer International Consortium (METABRIC) (whole database n = 1094, ER+ HER2-n = 1355, HER2+ n = 236, and TNBC n = 313), and GSE96058 (whole database n = 3069, ER+ HER2-n = 2277, HER2+ n = 392, and TNBC n = 155). These data were retrieved from the cBioPortal (https://www.cbioportal.org (accessed on 22 September 2022)) and the Gene Expression Omnibus (GEO) repository of the United States National Institutes of Health (https://www.ncbi.nlm.nih.gov/geo (accessed on 22 September 2022)), as previously described [45,46]. Gene expression data from 114 normal breast tissue samples were retrieved from the Genotype-Tissue Expression (GTex) Portal (https://gtexportal.org (accessed on 22 September 2022)) [47].…”
Section: Data Acquisitionmentioning
confidence: 99%